Multibeam bathymetry processed data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM56 - Stefanie Gaide; Christian dos Santos Ferreira; Paul Wintersteller (PANGAEA, 2025)
Swath sonar bathymetry data used for that dataset was recorded during RV MARIA S. MERIAN cruise MSM57/2 using Kongsberg EM 122 multibeam echosounder. The cruise took place between 02.07.2016 and 25.07.2016 off Svalbard and Greenland. The cruise investigated changes of the phyto- and bacterioplankton community along salinity gradients in Arctic fjords and the impact of such changes on biogeochemical fluxes and chemical modification of organic substrates and metabolites [DOI: 10.2312/cr_msm56]. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest creation of products and approval. During the MSM56 cruise, the hull-mounted Kongsberg EM122 multibeam echosounder (MBES) was utilized to perform bathymetric mapping in middle to deep water depths. Two linear transducer arrays in a Mills Cross configuration transmit acoustic signals of a nominal sonar frequency of 12 kHz. With 432 soundings per swath, the emission cone has a dimension of max 150° across track and 2° along track. With a reception obtained from 288 beams, the actual beam footprint is 2° by 2°. Depending on the roughness of the seafloor, the swath width on a flat bottom is generally maximum six times the water depth. For further information on the system, consult https://www.km.kongsberg.com/. Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, https://www.mbari.org/products/research-software/mb-system, 2017) was utilized for this purpose. A sound velocity correction profile was applied to the MSM56 data; there were no further corrections for roll, pitch and heave applied during postprocessing. A tide correction was applied, based on the Oregon State University (OSU) tidal prediction software (OTPS) that is retrievable through MB-System. CTD measurements during the cruise were sufficient to represent the changes in the sound velocity throughout the study area. Using Mbeditviz, artefacts were cleaned manually. NetCDF (GMT) grids of the edited data as well as statistics were created with mbgrid. The published bathymetric EM122 grid of the cruise MSM56 has a resolution of 35 m. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. The DTMs projections are given in Geographic coordinate system Lat/Lon; Geodetic Datum: WGS84.